(untitled) (Horizontes de Enfermería, 2023)
At present, there is a growing interest in addressing the impact of the COVID-19 pandemic on nursing staff. The prevalence of anxiety, depression, and the presence of post-traumatic syndrome in nursing professionals in the province of Carchi was investigated; through a descriptive cross-sectional study in a random sample of 229 nursing professionals. A survey was used that contains sociodemographic variables, the Hospital Anxiety and Depression scales (HADS), and the stressor impact scale (IES-R); the Pearson bivariate correlation test was used with a significance level of p<0.05. There is evidence of a young adult population with an age range between 29 to 38 years, 43.2% of single marital status, and (77.7%) with a third-level academic education with more than ten months of professional experience. According to the HADS scale, there are indications of the presence of anxious and depressive cognitive symptoms of type (48.85%); the (23.79%) of professionals with possible symptoms associated with depression, such as irritability, loss of interest or dissatisfaction in the performance of work activities, depression, and anxiety already exist in more than 15% of the population. Presence of post-traumatic stress, 32, 89% mild, and severe (9.61%). The study population spent close to 10 months in complete contact with COVID-19 patients, with a statistical value of (-0.058). Therefore, the greater the work experience, the less possibility of presenting post-traumatic stress (0.47).